THE UNSEEN EMBRACE: EMOTIONAL SUPPORT AND SELF-ACCEPTANCE AMONG MOTHERS OF CHILDREN WITH SPECIAL NEEDS - Keisha Indira Sophia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Mothers of children with special needs often face psychological challenges in accepting their child’s condition. Previous studies have shown that social support is associated with self-acceptance among parents of children with special needs. However, limited research has specifically examined emotional support as a distinct form of support separate from general social support, particularly among mothers who tend to experience greater emotional burdens in caregiving. This study aimed to examine the relationship between emotional support and self-acceptance among mothers of children with special needs and to identify the associations between the dimensions of both constructs. A quantitative correlational design was employed using snowball sampling involving mothers from various regions of Indonesia. The instruments consisted of a self-acceptance scale and an emotional support scale. Data were analyzed using Pearson Product Moment correlation. The results revealed a significant positive relationship between emotional support and self-acceptance. Dimensional correlation analysis showed that positive regard had the strongest association with unconditional love, while empathy had the strongest association with acceptance of uniqueness. These findings indicate that emotional support is positively associated with self-acceptance and may serve as an important psychosocial resource for mothers of children with special needs. Practically, the findings highlight the importance of family-based interventions that strengthen empathy and positive regard to support maternal self-acceptance. ABSTRAK Ibu yang memiliki anak berkebutuhan khusus sering menghadapi tantangan psikologis dalam menerima kondisi anak. Penelitian sebelumnya menunjukkan bahwa dukungan sosial berkaitan dengan penerimaan diri pada orang tua anak berkebutuhan khusus. Namun, penelitian yang secara khusus mengkaji dukungan emosional sebagai bentuk dukungan yang berbeda dari dukungan sosial umum masih terbatas, terutama pada ibu yang cenderung menghadapi beban emosional lebih besar dalam pengasuhan anak berkebutuhan khusus. Penelitian ini bertujuan untuk menguji hubungan antara dukungan emosional dan penerimaan diri pada ibu yang memiliki anak berkebutuhan khusus serta mengidentifikasi hubungan antar dimensi kedua variabel tersebut. Penelitian ini menggunakan metode kuantitatif korelasional dengan teknik snowball sampling yang melibatkan ibu dari berbagai wilayah di Indonesia. Instrumen penelitian terdiri atas skala penerimaan diri dan skala dukungan emosional. Data dianalisis menggunakan korelasi Pearson Product Moment. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara dukungan emosional dan penerimaan diri. Analisis korelasi antar dimensi menunjukkan bahwa penghargaan positif memiliki hubungan paling kuat dengan kasih sayang tak bersyarat, sedangkan empati memiliki hubungan paling kuat dengan penerimaan terhadap keunikan anak. Temuan ini menunjukkan bahwa dukungan emosional berkaitan secara positif dengan penerimaan diri dan dapat menjadi sumber daya psikososial penting bagi ibu yang memiliki anak berkebutuhan khusus. Secara praktis, hasil penelitian ini menegaskan pentingnya intervensi keluarga berbasis empati dan penghargaan positif untuk memperkuat penerimaan diri ibu.